Evaluation of sperm motility and velocity of different genetic groups of bucks using Computer-Assisted Sperm Analyzer (Bangladesh Journal of Animal Science, 2020)
Semen quality assessment is a prime prerequisite for any breeding programme. Computer-Assisted Sperm Analyzer (CASA) can measure the semen quality very accurately and sharply. The research was conducted at American Dairy Limited (ADL) at Vangnahati, Sreepur, Gazipur. A total of 120 ejaculates were collected from three genetic groups of bucks namely Black Bengal (BB), Boer and Jamunapari (JP) with a view to characterize and compare the semen motility and velocity parameters using Computer- Assisted Sperm Analyser. Significantly (p